Let the slope be m.

\(\displaystyle{m}=\frac{{{\underset{{{2}}}{{{y}}}}-{\underset{{{1}}}{{{y}}}}}}{{{\underset{{{2}}}{{{x}}}}-{\underset{{{1}}}{{{x}}}}}}\)

Substitute from the given:

\(\displaystyle{m}=\frac{{{6}-{3}}}{{{4}-{2}}}\)

\(\displaystyle{m}=\frac{{3}}{{2}}\)

\(\displaystyle{m}=\frac{{{\underset{{{2}}}{{{y}}}}-{\underset{{{1}}}{{{y}}}}}}{{{\underset{{{2}}}{{{x}}}}-{\underset{{{1}}}{{{x}}}}}}\)

Substitute from the given:

\(\displaystyle{m}=\frac{{{6}-{3}}}{{{4}-{2}}}\)

\(\displaystyle{m}=\frac{{3}}{{2}}\)